LIM kinase and metanephric mesenchymal cell migration in the developing mouse kidney - Sparrow, Alexander (2016)
The adult mammalian kidney forms from the reciprocal interaction between two tissues; the ureteric bud which will form the collecting duct system and the metanephric mesenchyme which will form all the cells in the nephrons. This thesis used ex-vivo embryonic kidney culture to show that during mouse kidney development metanephric mesenchymal cells migrated towards the periphery of the kidney. When this migration is pharmacologically inhibited the Six2 expressing metanephric mesenchyme cells no longer expanded their population and kidney development ceases. LIM kinase, which had been shown to regulate cell migration, when inhibited not only prevented cell migration in both embryonic mouse kidneys and in HK2 cells but also prevented embryonic kidney cells from completing mitosis and caused them to undergo apoptosis. This thesis showed that inhibition of LIM kinase in HK2 cells resulted in the formation of multiple alpha-tubulin foci, multiple centrosomes, the premature dispersal of the cohesin complex protein SMC3 in the absence of a fully formed spindle, and cell death. Thus concluding that active LIM kinase is required for the generation of the mitotic spindle and the appropriate dispersal of SMC3. This thesis furthered the understanding of how the metanephric mesenchyme develops and showed that these cells migrated away from the ureteric bud and this migration is required for further growth of the kidney. This thesis also showed that active LIM kinase is required for the completion of mitosis in both embryonic kidneys and HK2 cells.